THE LEGITIMACY OF THE PHENOMENON OF THE ESCALATION OF COMMERCIAL RIGHTS PROTECTION FOR SPORTS MEGA-EVENTS THROUGH THE MEANS OF SUI GENERIS LAWS AND THE DEVELOPMENT OF ‘ASSOCIATION RIGHTS’ TO THESE MEGA-EVENTS (The Pretoria Student Law Review, 2021)
In this article, I am, from a legal perspective, going to critically evaluate the creation, nature and working of such ‘association rights’ as contained in the relevant provisions in legislation such as the Merchandise Marks Act 17 of 1941 (as amended) and the Olympics Act (Law 12035 of 2009) as passed for the 2016 Rio Olympic Games (Brazil). I am going to critically evaluate the legitimacy of this phenomenon of escalation of commercial rights protection for sports mega-events through the means of sui generis laws, specifically in respect of its culmination in recent years with the development of socalled ‘association rights’ to these events. In order to enable a deeper understanding of my position on the aforementioned issue, I am first going to define ‘ambush marketing’ and other key concepts as this will enable the reader and I to have a common foundation and understanding. Furthermore, I am going to give an important theoretical understanding of commercial rights and sponsorship in sports to enable the reader to understand what is at stake when legislation creating association rights is passed and to show that there is this phenomenal spike in the protection of commercial rights. I am then going to proceed to finalise the issue by critiquing and evaluating as aforementioned.
Keywords: association rights; Merchandise Marks Act; Olympics Act; 2016 Rio Olympic Games; sports mega-events; commercial rights protection; sponsorship in sports